Role of Basic Learning Opportunities in Building Capacity for Inventiveness (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
The study examines the efficacy of capacity-building of basic learningopportunities in stimulating entrepreneurship inventiveness potentials of trainees. Twohypotheses were tested in the study at P < .05 significant level. The first hypothesisexamined gender differences in the efficacy of basic learning opportunities in buildingcapacity for inventiveness. The second hypothesis examined the various dimensions ofentrepreneurship inventiveness as a result of capacity building of basic learningopportunities. The data for the study was of primary source. A total of 348 Universitystudents, with the average age of 23 years, were randomly sampled for the study, fromtechnoscience disciplines, socio-behavioural disciplines, and managerial disciplines. Theywere challenged to provide answers to a learning exercise that embraced the triodisciplines. With multivariate analyses, it was found out that both genders have aboveaverage capacity-building to be inventive. However, the female gender developed morecapacity-building to be technically creative, and exhibit social skills inventiveness than themale gender. On the other hand, the male gender had more capacity-building for leadershipinventiveness than the female gender. Basically, the value system and motivation couldhave played significant roles in the outcome. It is therefore recommended that learningopportunities should be open and be encouraged for both genders across disciplines.
Keywords: basic-learning, capacity-building, inventiveness, cognition